2020
DOI: 10.1109/access.2020.3014863
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support System for Classification Medullary Thyroid Cancer

Abstract: Due to the complex, heterogeneous and mimic morphological features of medullary thyroid cancer (MTC). It becomes often difficult to diagnose MTC at early stage. Since histopathological complex patterns of cancerous cells and tissues requires a huge effort to classify. Therefore thyroid cancer classification has become one of the significant research area area(s) of Machine Learning. We propose a decision support system to classify initial variation of morphological appearance of nuclei by using Convolutional N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Wang et al [24] found 97.34% and 94.42% accuracy in VGG-19 and Inception-ResNet-v2 models, demonstrating the usefulness of sophisticated neural network architectures (see Table III). Chandio et al [39] developed a CNN-based decision support system with 99.00% accuracy for thyroid cancer diagnosis. Hossiny et al [25] achieved 98.74% accuracy using cascaded CNN and split classification.…”
Section: A Comparative Study With Our Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [24] found 97.34% and 94.42% accuracy in VGG-19 and Inception-ResNet-v2 models, demonstrating the usefulness of sophisticated neural network architectures (see Table III). Chandio et al [39] developed a CNN-based decision support system with 99.00% accuracy for thyroid cancer diagnosis. Hossiny et al [25] achieved 98.74% accuracy using cascaded CNN and split classification.…”
Section: A Comparative Study With Our Proposed Methodsmentioning
confidence: 99%
“…CNNs are powerful deep neural networks for visual analysis. They excel in automatically detecting and learning spatial hierarchies of characteristics from pictures, which is essential for thyroid cancer detection in medical imaging [39]. Convolutional, pooling, and fully linked layers make up a CNN.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…Jamil Ahmed Chandio et al [8]: This paper addresses the classification problem of Medullary Thyroid Cancer and classifies malignant and non-malignant cells and tissues. The proposed methodology of this paper is based upon three layers.…”
Section: Classificationmentioning
confidence: 99%
“…Decision Trees are based on the Sum of Product (SOP) representation. Each branch from the tree's core to a leaf node along with the category is an intersection (product) of weights and dissimilar branches terminate in that category form a predicate (sum) (16) . The foremost challenge in executing a decision tree is deciding which features should be recognized for the root node at every level (17) - (18) .…”
Section: 3decision Treementioning
confidence: 99%